Seasonal and life-stage variation in the reproductive ecology of a marine apex predator, the tiger shark Galeocerdo cuvier, at a protected female-dominated site - JA Sulikowski (Inter-Research, 2016)
Advancing our knowledge of the reproductive biology and mating systems of free-ranging sharks is inherently challenging. The large size and mobility of the specimens are just a few of the problems that make such studies complicated, and in some respects, impractical. The tiger shark Galeocerdo cuvier is a large, roving, apex predator found in many oceans throughout the world. Although their nomadic nature is primarily linked to large-scale migrations, these sharks can also display site fidelity. One site where this is known to occur is at Tiger Beach, Bahamas. Unique to the waters of this area is the consistent sighting of large females. While the sex-specific use of the area remains unknown, the shallow, warm environment could represent a critical habitat for reproductive events. To investigate the reproductive biology of tiger sharks at Tiger Beach, 65 individuals were opportunistically sampled between 2011 and 2014. Reproductive status of captured females (n = 59) was assessed with ultrasonography and by measuring circulating sex steroid hormones (progesterone, testosterone and estradiol). Our results indicate that Tiger Beach is a high-use site for female tiger sharks of mixed life stages. The results also suggest that Tiger Beach may function as a refuge habitat, allowing females to reach maturity free from male mating harassment, as well as functioning as a gestation ground where gravid females can benefit from year-round calm warm waters, which may reduce the gestation period and accelerate embryo development.